Patient and transplant outcome in infants starting renal replacement therapy before 2 years of age. Issue 8 (29th March 2018) - Hogan, Julien; Bacchetta, Justine; Charbit, Marina; Roussey, Gwenaelle; Novo, Robert; Tsimaratos, Michel; Terzic, Joelle; Ulinski, Tim; Garnier, Arnaud; Merieau, Elodie; Harambat, Jérôme; Vrillon, Isabelle; et al.
Abstract: Background: Despite major technical improvements in the care of children requiring renal replacement therapy (RRT) before 2 years of age, the management of those patients remains challenging and transplantation is generally delayed until the child weighs 10 kg or is 2 years old. In this national cohort study, we studied patient and graft survival in children starting RRT before 2 years of age to help clinicians and parents when deciding on RRT initiation and transplantation management. Methods: All children starting RRT before 24 months of age between 1992 and 2012 in France were included through the national Renal Epidemiology and Information Network (REIN) registry. The primary endpoints were patient survival on dialysis and 10-year graft survival. Results: A total of 224 patients were included {62% boys, median age 10.5 months [interquartile range (IQR) 5.8–15.6]}. The 10-year survival rate was 84% (IQR 77–89). Suffering from extrarenal comorbidities was the only factor significantly associated with both an increased risk of death on dialysis [hazard ratio 5.9 (95% confidence interval 1.8–19.3)] and a decreased probability of being transplanted. During follow-up, 174 renal transplantations were performed in 171 patients [median age at first transplantation 30.2 (IQR 21.8–40.7) months]. The 10-year graft survival was 74% (IQR 67–81). Factors associated with graft loss in multivariate analysis were the time spent on dialysis before transplantation, donor/recipient height ratio with an increased risk for both small and tall donors and presenting two human leucocyte antigen–antigen D-related mismatches. Conclusions: This study confirms the good outcome of children starting RRT before 2 years of age. The main question remains when and how to transplant those children. Our study provides data on the optimal morphological and immunological matching in order to help clinicians in their decisions.